Targeting an Alcohol Intervention Cost‐Effectively to Persons Living with HIV/AIDS in East Africa. (14th October 2015) - Kessler, Jason; Ruggles, Kelly; Patel, Anik; Nucifora, Kimberly; Li, Lifeng; Roberts, Mark S.; Bryant, Kendall; Braithwaite, R. Scott
Abstract : Background: In the current report, we ask if targeting a cognitive behavioral therapy (CBT)‐based intervention aimed at reducing hazardous alcohol consumption to HIV‐infected persons in East Africa would have a favorable value at costs that are feasible for scale‐up. Methods: Using a computer simulation to inform HIV prevention decisions in East Africa, we compared 4 different strategies for targeting a CBT intervention—(i) all HIV‐infected persons attending clinic; (ii) only those patients in the pre‐antiretroviral therapy (ART) stages of care; (iii) only those patients receiving ART; and (iv) only those patients with detectable viral loads (VLs) regardless of disease stage. We define targeting as screening for hazardous alcohol consumption (e.g., using the Alcohol Use Disorders Identification Test and offering the CBT intervention to those who screen positive). We compared these targeting strategies to a null strategy (no intervention) or a hypothetical scenario where an alcohol intervention was delivered to all adults regardless of HIV status. Results: An intervention targeted to HIV‐infected patients could prevent 18, 000 new infections, add 46, 000 quality‐adjusted life years (QALYs), and yield an incremental cost‐effectiveness ratio of $600/QALY compared to the null scenario. Narrowing the prioritized population to only HIV‐infected patients in pre‐ART phases of care results in 15, 000 infections averted, the addition of 21, 000 QALYs and would be cost‐saving, while prioritizing based on an unsuppressed HIV‐1 VL test results in 8, 300 new infections averted, adds 6, 000 additional QALYs, and would be cost‐saving as well. Conclusions: Our results suggest that targeting a cognitive‐based treatment aimed at reducing hazardous alcohol consumption to subgroups of HIV‐infected patients provides favorable value in comparison with other beneficial strategies for HIV prevention and control in this region. It may even be cost‐saving under certain circumstances.